(untitled) (Spanish Yearbook of International Law, 2011)
Since Spain’s democratization this State has ratified many human rights treaties. Currently, Spain is bound by nine universal human rights treaties. They provide for substantive human rights obligations as well as for periodic reporting mechanisms. These reporting mechanisms are assigned to the United Nations Human Rights Council. In addition, in early 2010 the Human Rights Council has scrutinized for the first time the human rights situation in Spain in the context of the Universal Periodic Review. Spain’s practice before all these mechanisms raises questions such as the timeliness of Spain’s submission of reports, the authorship and contents of reports, the participation of national human rights institutions as well as civil society in the drafting stage and the public discussion of reports, as well as the practical implications of these procedures in Spain’s human rights practice. The present study will consider all these issues, and it will identify good practices and make suggestions for improvement of the Spanish practice.